DNA polymerase α-primase facilitates PARP inhibitor-induced fork acceleration and protects BRCA1-deficient cells against ssDNA gaps - Machacova, Zuzana; Chroma, Katarina; Lukac, David; Protivankova, Iva; Moudry, Pavel (Nature communications, 2024)
PARP inhibitors (PARPi), known for their ability to induce replication gaps and accelerate replication forks, have become potent agents in anticancer therapy. However, the molecular mechanism underlying PARPi-induced fork acceleration has remained elusive. Here, we show that the first PARPi-induced effect on DNA replication is an increased replication fork rate, followed by a secondary reduction in origin activity. Through the systematic knockdown of human DNA polymerases, we identify POLA1 as mediator of PARPi-induced fork acceleration. This acceleration depends on both DNA polymerase α and primase activities. Additionally, the depletion of POLA1 increases the accumulation of replication gaps induced by PARP inhibition, sensitizing cells to PARPi. BRCA1-depleted cells are especially susceptible to the formation of replication gaps under POLA1 inhibition. Accordingly, BRCA1 deficiency sensitizes cells to POLA1 inhibition. Thus, our findings establish the POLA complex as important player in PARPi-induced fork acceleration and provide evidence that lagging strand synthesis represents a targetable vulnerability in BRCA1-deficient cells.
Keywords: DNA-Directed DNA Polymerase; DNA Polymerase I; DNA, Single-Stranded; lidé; DNA-polymerasa I; DNA-dependentní DNA-polymerasy; DNA Primase; DNA-primasa; replikace DNA; PARP inhibitory; Poly(ADP-ribose) Polymerase Inhibitors; jednovláknová DNA; DNA Replication; Cell Line, Tumor; protein BRCA1; nádorové buněčné linie; BRCA1 Protein; Humans